The Present and Future of Financial Studies: Institute of Finance - Marcinkowska, Monika; Szymańska, Anna (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and current activity of the Institute of Finance at the Faculty of Economics and Sociology, University of Łódź. The authors discuss its academic and teaching traditions, with particular focus on the last ten years.